PENGARUH KREDIT USAHA RAKYAT, TENAGA KERJA DAN TEKNOLOGI TERHADAP PRODUKTIVITAS USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KOTA DENPASAR - Sari, Leony Puspitha; Arka, Sudarsana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia are one of the priorities in national economic development, apart from being the backbone of the people's economic system which is not only aimed at reducing the problem of inequality between income groups and between business actors, or poverty alleviation and employment. . In connection with the above, it can be stated that the purpose of this research is to analyze the effect of people's business credit, labor and technology simultaneously and partially on the productivity of Micro, Small and Medium Enterprises (MSMEs) in Denpasar City. This research was conducted in Denpasar City, with a total sample of 100 SMEs. Data collection in this study was carried out through observation, structured interviews, and in-depth interviews. The analysis technique used is multiple linear regression analysis technique. The results showed that, 1) People's business credit, labor, and technology simultaneously had a significant effect on the productivity of Micro, Small and Medium Enterprises (MSMEs) in Denpasar City. 2) People's business credit, labor and technology partially have a positive and significant effect on the productivity of Micro, Small and Medium Enterprises (MSMEs) in Denpasar City.